THE EFFECT OF PROFITABILITY, LIQUIDITY AND CAPITAL STRUCTURE ON COMPANY VALUE WITH COMPANY SIZE AS MODERATION - Pangestuti, Tania Ayu Dwi; Widiarsono, Salsa Billa Adi; Fitriyah, Putri Lailatul; Nurasik (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The purpose of this research is to examine the influence of profitability, liquidity, and capital structure on company value with moderation of company size. Method: The data used is secondary data from the IDX on garment and textile companies for 2018-2022. The population in the study was 22 companies, and 11 samples were obtained using purposive sampling techniques. Hypothesis testing uses SmartPLS 3. Results: The results of this research state that profitability and capital structure have no effect on company value, while liquidity has an effect on company value. Company size is able to moderate profitability but cannot moderate liquidity and capital structure. Novelty: This study highlights the moderating role of company size in the relationship between financial indicators and company value, specifically its ability to moderate profitability while having no moderating effect on liquidity and capital structure.